Cell-to-cell and long-distance trafficking of the green fluorescent protein in the phloem and symplastic unloading of the protein into sink tissues. - Imlau, Astrid; Truernit, Elisabeth; Sauer, Norbert (The Plant Cell, 1999)
Macromolecular trafficking within the sieve element-companion cell complex, phloem unloading, and post-phloem transport were studied using the jellyfish green fluorescent protein (GFP). The GFP gene was expressed in Arabidopsis and tobacco under the control of the AtSUC2 promoter. In wild-type Arabidopsis plants, this promoter regulates expression of the companion cell-specific AtSUC2 sucrose-H+ symporter gene. Analyses of the AtSUC2 promoter-GFP plants demonstrated that the 27-kD GFP protein can traffic through plasmodesmata from companion cells into sieve elements and migrate within the phloem. With the stream of assimilates, the GFP is partitioned between different sinks, such as petals, root tips, anthers, funiculi, or young rosette leaves. Eventually, the GFP can be unloaded symplastically from the phloem into sink tissues, such as the seed coat, the anther connective tissue, cells of the root tip, and sink leaf mesophyll cells. In all of these tissues, the GFP can traffic cell to cell by symplastic post-phloem transport. The presented data show that plasmodesmata of the sieve element-companion cell complex, as well as plasmodesmata into and within the analyzed sinks, allow trafficking of the 27-kD nonphloem GFP protein. The data also show that the size exclusion limit of plasmodesmata can change during organ development. The results are also discussed in terms of the phloem mobility of assimilates and of small, low molecular weight companion cell proteins.